Identifying Pyroclastic Density Currents From Partial Outcrop Exposure on Mt. Ruapehu, New Zealand - Gillies, Janina; Kennedy, Ben M.; Gravley, Darren M.; Leonard, Graham; Cowlyn, James (Frontiers in Earth Science, 2020)
Mt Ruapehu is one of New Zealand’s most active volcanoes, last erupting in 2007. Few studies have investigated the pyroclastic density current (PDC) occurrence on this volcano, despite PDCs being one of the most hazardous volcanic processes. Poor preservation of PDC deposits, due to past glaciations, erosion, burial, and poor consolidation has left a significant gap in Mt Ruapehu’s eruptive record. By identifying and characterising PDCs on Mt Ruapehu this paper provides an updated account of PDC occurrence on this volcano. Comprehensive field-mapping forms the basis for this study by identifying PDC deposits from partial outcrop exposures. We use field observations of these deposits to describe the lithofacies and infer PDC behaviour. Relative stratigraphy and whole-rock geochemistry are used to correlate deposits with dated units from literature and provide approximate age ranges. This study found 12 PDC deposits representing at least 10 previously unidentified flows. Combined with PDCs identified in previous studies there is a total of 23 PDC deposits found on Mt Ruapehu, including the PDC observed during the 1945 eruption. These PDCs have been emplaced throughout Mt Ruapehu’s 250 ka eruptive history. The PDCs were concentrated and dominated by granular flow or granular fluid-based flow transport regimes. The lithofacies show PDCs forming from column collapse and dome collapse or explosion events. This demonstrates that Mt Ruapehu is capable of producing a spectrum of PDC styles, something that must be considered during future hazard planning on the volcano.